Evaluation of inbred lines of maize (Zea mays L.) through line × tester method (Bangladesh Journal of Agricultural Research, 2015)
Maize inbred lines were evaluated by using line × tester method involving 11 lines and 3 testers for grain yield and its components through estimation of general combining ability (gca) and specific combining ability (sca) effects. Highly significant genotypic differences were observed indicated wide range of variability present among the genotypes. The crosses with high sca effect for grain yield were evolved from high × low general combiner parents which reveled additive × dominance type of gene action. The cross combinations 9MS4-1 × L22, 9MS4-1 × L486, 9MS4-2 × L431, 9MS4-11 × L486 and 9MS4- 15 × L431 with high positive sca effect having high mean values might be used for obtaining high yielding hybrids. The information on the nature of gene action with respective variety and characters might be used depending on the breeding objectives. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22547 Bangladesh J. Agril. Res. 39(4): 675-683, December 2014